How do you solve 4x-3 (2x+5) = -5?

admin 49 0

X=-5/1=-5=-5.0

PREMISES

4x-3(2x+5)=-5

CALCULATIONS

4x-3(2x+5)=-5

Denoting the order of operations from left to right,

4x-6x-15=-5

Isolating the variable on the LHS,

-2x=-5+15

-2x=10

Solving,

-2x/-2=10/-2

x=10/-2

x=

-5/1=-5=-5.0

PROOF

If x=-5, then the mathematic sentence 4x-3(2x+5)=-5 brings

4(-5)-3[2(-5)+5]=-5

-20–3(-10+5)=-5

-20–3(-5)=-5

-20+15=-5 and

-5=-5 supports the solution x=-5 to the sentence

C.H.

Post comment 0Comments)

  • Refresh code

No comments yet, come on and post~